(untitled) (Research, Society and Development, 2021)
Clinical research is important for understanding pathologies and discovering therapeutic innovations. In Brazil, although it is expanding and has aroused interest in researchers and institutions, especially in this period of the COVID-19 pandemic, it is still characterized as a new area, and in many regions of the country there is a lack of research that prioritizes the demand for diseases of national importance. Thus, the aim of this study was to map clinical research centers in addition to studies on this topic, focusing on the northern region of Brazil. The study was carried out by searching the database of the CNPQ Directory of Research Groups, Brazil Platform, National Health Surveillance Agency, National Network of Clinical Research, Brazilian Registry of Clinical Trials and ClinicalTrials.gov. The North region, although having relevant centers, these in number are inferior to other regions of Brazil. Likewise, in the state of Tocantins, clinical studies are still a modest reality. In this sense, the need for an equal distribution of research centers in the country and investments in clinical studies, especially in Tocantins is highlighted, as there are several demands in the national territory due to regional differences in the population and potential of each location.